Perceptions of Indian Physicians towards Deprescribing of Medications for Chronic Diseases in Elderly: A Questionnaire-based Study - Jawahar, Shribhavana; Selvaraj, Lakshmipriya; Muruganantham, Kailash; Kumar, Iniya; Nagasubramanian, Vanitha Rani (Indian Journal of Pharmaceutical Education and Research, 2023)
Deprescribing is the process of reconstructing multiple medications use by review and analysis, which concludes with the modification, replacement or elimination of drugs. Medications that were once appropriate may become inappropriate due to age-related physiological changes that increase the risk of harm from medications eliminated by the liver and kidneys and other co-morbidities. In India, with a steadfast rise in the elderly population paralleled with an augmented necessity for chronic disease management, the essence of deprescribing is rarely known and less practiced by physicians. Hence, a questionnaire-based interventional study was conducted to assess their perception and attitude towards implementing the deprescribing process. The study included 75 physicians from the departments of General Medicine and Nephrology, who were initially educated on deprescribing through a self-developed and validated educational video of three minutes duration, following which they were asked to fill the Perceptions, Attitudes and Challenges of Physicians towards Deprescribing Questionnaire. About 76% of the physicians felt that deprescribing was needed to reduce medication-related problems in older patients. Involvement of multiple prescribers (54.6%) was the main challenge stated by physicians; 92% stated deprescribing to be beneficial in current clinical scenario, and 85.3% showed a positive attitude towards integrating deprescribing into their day-to-day clinical practice. Physicians below 40 years with an experience of 0 to 10 years had a significantly positive perception and attitude towards deprescribing. In view of reducing potential medication-related adverse events in the elderly, daily practice of the deprescribing process should become a norm, thereby improving the quality of life.
Keywords: Comorbidities; Polypharmacy; Deprescribing; Elderly patients